Families, Schools, and Primary-School Learning : Evidence for Argentina and Colombia in an International Perspective - Woessmann, Ludger; Fuchs, Thomas (World Bank, Washington, DC, 2012)
This paper estimates the relationship between family background, school characteristics, and student achievement in primary school in two Latin American countries, Argentina and Colombia, as well as several comparison countries. The database used is the student-level international achievement data of the Progress in International Reading Literacy Study (PIRLS), which tested the reading performance of fourth-grade students in 2001. The nationally representative samples have 3,300 students in Argentina and 5,131 students in Colombia. The emerging general pattern of results is that educational performance is strongly related to students' family background, weakly to some institutional school features, and hardly to schools' resource endowments. In an international perspective, estimated family background effects are relatively large in Argentina, and relatively small in Colombia. A specific Argentine feature is the lack of performance differences between rural and urban areas. A specific Colombian feature is the lack of significant differences between gender performance. Nonnative students and students not speaking Spanish at home have particularly weak performance in both countries. But there are no differences by parental occupation and no positive effects of kindergarten attendance. In Argentina, students perform better in schools with a centralized curriculum and ability-based class formation.